Regulation of RNA Polymerase II Transcription Initiation and Elongation by Transcription Factor TFII-I - Linzer, Niko; Trumbull, Alexis; Nar, Rukiye; Gibbons, Matthew D.; Yu, David T.; Strouboulis, John; Bungert, Jörg (Frontiers in Molecular Biosciences, 2021)
Transcription by RNA polymerase II (Pol II) is regulated at different levels including chromatin structure alterations, interactions between distal regulatory elements and promoters, formation of transcription domains enriched for Pol II and co-regulators, and mechanisms involved in transcription initiation, elongation, and termination. Transcription factor TFII-I, originally identified as an initiator (INR) binding protein, contains multiple protein-protein interaction domains and plays diverse roles in transcription regulation. Genome-wide analysis revealed that TFII-I associates with expressed as well as repressed genes. Consistently, TFII-I interacts with co-regulators that either positively or negatively regulate transcription. Furthermore, TFII-I has been shown to regulate transcription pausing by interacting with proteins that promote or inhibit transcription elongation. Changes in TFII-I expression in humans are associated with neurological and immunological diseases as well as cancer. Furthermore, TFII-I is essential for mouse development and represents a barrier for the induction of pluripotency. Here, we review the known functions of TFII-I related to the regulation of Pol II transcription at the initiation and elongation steps.